2011
DOI: 10.1074/jbc.m110.167254
|View full text |Cite
|
Sign up to set email alerts
|

The Dimeric SOS Mutagenesis Protein UmuD Is Active as a Monomer

Abstract: The homodimeric umuD gene products play key roles in regulating the cellular response to DNA damage in Escherichia coli. UmuD 2 is composed of 139-amino acid subunits and is up-regulated as part of the SOS response. Subsequently, damage-induced RecA⅐ssDNA nucleoprotein filaments mediate the slow self-cleavage of the N-terminal 24-amino acid arms yielding UmuD 2 . UmuD 2 and UmuD 2 make a number of distinct protein-protein contacts that both prevent and facilitate mutagenic translesion synthesis. Wild-type UmuD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…In E. coli , UmuD forms dimers that cleaves intermolecularly (McDonald et al ., ), although recent evidence shows that E. coli UmuD can cleave intramolecularly, albeit only when a specific mutation is engineered into UmuD to prevent homodimerization (Ollivierre et al ., ). However, we found that UmuDAb, unlike UmuD, does not cleave intermolecularly, although UmuDAb contains the conserved asparagine required for UmuD dimerization (Ollivierre et al ., ). In this respect, UmuDAb naturally behaves like a monomer, although its homology to other self‐cleaving serine proteases supports the hypothesis that it may dimerize.…”
Section: Resultsmentioning
confidence: 97%
“…In E. coli , UmuD forms dimers that cleaves intermolecularly (McDonald et al ., ), although recent evidence shows that E. coli UmuD can cleave intramolecularly, albeit only when a specific mutation is engineered into UmuD to prevent homodimerization (Ollivierre et al ., ). However, we found that UmuDAb, unlike UmuD, does not cleave intermolecularly, although UmuDAb contains the conserved asparagine required for UmuD dimerization (Ollivierre et al ., ). In this respect, UmuDAb naturally behaves like a monomer, although its homology to other self‐cleaving serine proteases supports the hypothesis that it may dimerize.…”
Section: Resultsmentioning
confidence: 97%
“…3C). We previously observed that plasmid-borne umuC can suppress the extreme sensitivity to UV that is characteristic of strains in which both umuC and recJ have been deleted (19,48). RecJ helps to partially degrade DNA at replication forks that are stalled due to lesions to help aid in restart of DNA replication.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work suggests that UmuD′ can be active as a monomer [90]. It is not unreasonable to imagine that an UmuD′C/RecA complex lacking distal UmuD′ (darker green in Figure 6) might still retain activity.…”
Section: Resultsmentioning
confidence: 99%